Bedtime misalignment and progression of breast cancer*. (March 2014) - Hahm, Bong-Jin; Jo, Booil; Dhabhar, Firdaus S.; Palesh, Oxana; Aldridge-Gerry, Arianna; Bajestan, Sepideh N.; Neri, Eric; Nouriani, Bita; Spiegel, David; Zeitzer, Jamie M.
<x xml:space="preserve">Abstract</x> Disruption of circadian rhythms, which frequently occurs during night shift work, may be associated with cancer progression. The effect of chronotype (preference for behaviors such as sleep, work, or exercise to occur at particular times of day, with an associated difference in circadian physiology) and alignment of bedtime (preferred vs. habitual), however, have not yet been studied in the context of cancer progression in women with breast cancer. Chronotype and alignment of actual bedtime with preferred chronotype were examined using the Morningness–Eveningness Scale (MEQ) and sleep-wake log among 85 women with metastatic breast cancer. Their association with disease-free interval (DFI) was retrospectively examined using the Cox proportional hazards model. Median DFI was 81.9 months for women with aligned bedtimes ("going to bed at preferred bedtime") (n = 72), and 46.9 months for women with misaligned bedtimes ("going to bed later or earlier than the preferred bedtime") (n = 13) (log rank p = 0.001). In a multivariate Cox proportional hazard model, after controlling for other significant predictors of DFI, including chronotype (morning type/longer DFI; HR = 0.539, 95% CI = 0.320–0.906, p = 0.021), estrogen receptor (ER) status at initial diagnosis (negative/shorter DFI; HR = 2.169, 95% CI = 1.124–4.187, p = 0.028) and level of natural-killer cell count (lower levels/shorter DFI; HR = 1.641, 95% CI = 1.000–2.695, p = 0.050), misaligned bedtimes was associated with shorter DFI, compared to aligned bedtimes (HR = 3.180, 95% CI = 1.327–7.616, p = 0.018). Our data indicate that a misalignment of bedtime on a daily basis, an indication of circadian disruption, is associated with more rapid breast cancer progression as measured by DFI. Considering the limitations of small sample size and study design, a prospective study with a larger sample is necessary to explore their causal relationship and underlying mechanisms.